Assessing the impact of wildlife conservation areas on human well-being - Domenic Romanello; Heriniaina M. Rakotohary; Mirana J. E. Rahariniaina; Rebecca J. Lewis (PLoS ONE, 2026)
Effective wildlife conservation is inextricably linked to the well-being of people living in and around conservation areas. Historically, conservationists have focused on a narrow range of externally defined socio-economic proxies for human well-being, failing to provide the affected population with the opportunity to assess their own life and connection to local conservation interventions. If conservation area assessments do not faithfully detect the complex and multidimensional nature of human well-being, conservation policies and practices may be misaligned with the core objectives of conservation and detrimental to the rights and livelihoods of local communities. To address this concern, we evaluated the relationship between income, multidimensional poverty, and human well-being in 594 households (1,362 individuals) bordering Kirindy Mitea National Park, Madagascar. The vast majority of local community members (86% of households) lived below the international poverty line of 2.15 US$ per day, and nearly all (95% of households) were multidimensionally ‘impoverished,’ enduring severe health, education, and living standards deprivation. Human well-being, measured using the Global Person Generated Index (GPGI), was low, with a median of 5.25 (IQR 3.25–7.00; scale range: 0.00–10.00). Higher income was associated with lower multidimensional poverty (χ² = 14.57, df = 3, p = 0.002, ε² = 0.02) and higher well-being (ρ = 0.14, p < 0.001), but multidimensional poverty was unrelated to well-being (χ² = 3.81, df = 3, p = 0.283, ε² = 0.001). Perceptions of the park were largely negative: more than 80% of households reported no benefit to income or overall well-being, and costs such as displacement and loss of access to land and resources were widely cited. Local priorities for improving well-being centered on employment, financial assistance, food security, and agricultural support, complemented by strong demand for improved healthcare, education, and community infrastructure. Our study highlights substantial human costs associated with stringent environmental protections and illustrates the importance of integrating assessments of human well-being together with socio-economic evaluations of conservation areas.